On Fully Stable Banach Algebra Modules and Fully Pesudo Stable Banach Algebra Modules (Baghdad Science Journal, 2018)
The concept of fully pseudo stable Banach Algebra-module (Banach A-module) which is the generalization of fully stable Banach A-module has been introduced. In this paper we study some properties of fully stable Banach A-module and another characterization of fully pseudo stable Banach A-module has been given.